How Can Newborn Toxicology Testing Be More Equitable? An Interactive Ethics Workshop - Kelsey Ryan; Rakhi Gupta Basuray; Christy Cummings (Association of American Medical Colleges, 2024)
Introduction Practice variation in newborn toxicology testing during the birth hospitalization exists across institutions and legal jurisdictions. While testing can provide benefits, indiscriminate testing has been shown to perpetuate health care inequities. In the backdrop of an opioid epidemic and a charged medicolegal landscape, this workshop guides participants to reexamine newborn toxicology testing through a shared ethical lens. Methods We conducted a live, 90-minute workshop in English at an international pediatric conference. Physicians, residents, and fellows participated in large- and small-group breakout sessions to learn relevant clinical and bioethical frameworks, share their own local context and expertise, and explore ethical applications through case-based discussions. We administered two anonymous online follow-up surveys to assess self-perceived impact on participant knowledge, behavior, and clinical practice. Results Seven facilitators and 45 individuals participated in the workshop. Eighteen participants completed survey 1 immediately following workshop conclusion, and six participants completed survey 2 after 3 months had elapsed. Immediately following the workshop, 94% of respondents reported that they had been introduced to a new idea, and 82% were considering practice change. A low response rate to survey 2 limited interpretation, but some respondents reported self-perceived change following workshop attendance. Discussion This workshop facilitated conversation between physician participants on a complex pediatric health care inequity issue using an ethical framework.